Interlocked host molecules for anion recognition and sensing - Caballero, A; Zapata, F; Beer, P (2013)
This review describes the concept and exploitation of a strategic anion templation methodology in the construction of a range of interlocked host molecular frameworks designed to recognize anionic guest species in competitive aqueous media. Rotaxane and catenane receptors that contain unique anion binding cavity domains are demonstrated to exhibit high levels of anion selectivity in aqueous media. The incorporation of redox-active ferrocene and photo-active transition metal bipyridyl and naphthalene groups into interlocked host structures enables such materials to selectively sense anions by electrochemical and optical means. Importantly, halogen bonding interlocked host systems are shown to display enhanced anion recognition properties when compared with hydrogen bonding analogues. The assembly of interlocked architectures capable of displaying anion induced molecular motion, and of increased complexity, such as [3]rotaxanes and a handcuff catenane serves to further illustrate the scope and versatility of this anion templation approach. © 2013 .